1976
DOI: 10.2134/agronj1976.00021962006800020034x
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Nutrition and Yield of Sugarcane as Affected by N‐Serve1

Abstract: Very few experiments have been conducted to evaluate N‐Serve [2‐chloro‐6‐(trichloromethyl) pyridine] formulated with N fertilizer for sugarcane (Saccharum officirarum L.). N‐Serve when fomulated with N‐fertilizer increased sugarcane yields in the Philippines and in Louisiana but failed to do so in Puerto Rico and in Mauritius. In view of the relatively few experiments conducted with N‐Serve for sugarcane and the conflicting nature of the results, a pot experiment in drums and a field experiment were conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1978
1978
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…[25][26][27][28][29] Details of the seed and sowing/transplanting specifications are given in Table 13. In this experiment, the scented rice variety "Pusa Sugandh 5" [12,55] was planted during both the years. To maintain the same growth stage of rice in all the three CEMs, sowing of rice in ARS in main field and sowing of rice in the nursery for transplanting in PTR and SRI were done on the same date (the third week of June in both the years of study).…”
Section: Wwwglobal-challengescommentioning
confidence: 99%
“…[25][26][27][28][29] Details of the seed and sowing/transplanting specifications are given in Table 13. In this experiment, the scented rice variety "Pusa Sugandh 5" [12,55] was planted during both the years. To maintain the same growth stage of rice in all the three CEMs, sowing of rice in ARS in main field and sowing of rice in the nursery for transplanting in PTR and SRI were done on the same date (the third week of June in both the years of study).…”
Section: Wwwglobal-challengescommentioning
confidence: 99%
“…There are indications that nitrapyrin may be more effective in controlling nitrification in soils with higher clay contents than in soils with lower clay contents (Bundy and Bremner, 1973). Some authors (Geronimo et al, 1973;Goring, 1962;Prasad, 1976;Rieck and Lynd, 1967;Touchton et al, 1978a) have reported differences in nitrification or crop response among soils with various pH values when equal rates of N and nitrapyrin were applied to each soil. However, with one exception, soil pH was not the primary variable investigated, and the difference in nitrification or crop response among soils was generally not attributed to the possible effect of pH on the loss of nitrapyrin from the soil.…”
mentioning
confidence: 99%